An application of the caritative caring approach – nursing students' experiences of practising caring and uncaring encounters by simulation at a clinical training centre. Issue 1 (31st December 2022) - Knutsson, Susanne; Axelsson, Johanna; Lindqvist, Gunilla
ABSTRACT: Purpose: Nurses' lack of competence to be caring affects patients' health and patients describe a desire for more individual and compassionate care. Nursing education tends, however, to focus less on the caring approach in nursing practice and more on developing knowledge in psychomotor skills. The aim of this study was to describe nursing students' experiences of simulating caring and uncaring encounters founded on the caritative perspective at a Clinical Training Centre (CTC). Method: A qualitative, inductive approach using a qualitative latent content analysis. Written reflections of 49 students were analysed. Findings: By intertwining reflection with acting and observation, the students experienced that they achieved an open mind and gained an understanding of how important it was to treat the patient based on a caring approach. To act, first uncaring and thereafter caring, gave them an awakening. The students were touched and an overwhelming feeling of suddenly understanding human uniqueness and vulnerability appeared. Conclusions: To simulate caritative caring and uncaring encounters at the CTC enhanced students' knowledge and understanding about caring and strengthened their prerequisites to acquire a caritative ontological basic view and attitude which in the long run may lead to an increased feeling of patient well-being in the encounter.